RESULTS OF EXPERIMENTAL RESEARCHES FROM DETERMINATION OF HAULING EFFORT OF WORKINGS ORGANS OF TUBE CONVEYER - Токарчук, О. А. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The developed constructions of workings organs and chart of the experimental setting of tube conveyer, and also method of leadthrough of laboratory researches, are presented in the article. The results of experimental researches are resulted from determination of change of size of hauling effort of working organ on the different areas of technological route at application of different types of scrapers. Keywords: puck scrapers, tube conveyer, hauling effort, components of friable mixtures.